La hiperactividad y su incidencia en el rendimiento escolar de los niños y niñas de 4 y 5 años de la escuela Virgen del Quinche de la parroquia Poalo, cantón Latacunga, provincia de Cotopaxi en el periodo 2014-2015 - Medina Naranjo, María Teresa (2015)
For many years the hyperactivity has caused serious problems in schools, in these complications are involved teachers, students and parents. The problems presented in the educational environment are given by the ignorance of many teachers about hyperactivity and behavior disorders in children, which is reflected in academic performance and socio-emotional relations with the environment. The present research has a purpose to improve the academic performance of hyperactive children at "Virgen del Quinche" in school, through technical-experimental analysis, we determined how hyperactivity influences in educative processes and socialization in the school. With the implementation and application of assessment tools about teaching-learning process….